2010
DOI: 10.1029/2009gl041835
|View full text |Cite
|
Sign up to set email alerts
|

Seismic structure of the Longmen Shan region from S‐wave tomography and its relationship with the Wenchuan Ms 8.0 earthquake on 12 May 2008, southwestern China

Abstract: [1] Using arrival time data, we determined seismic structure of the Longmen Shan by S-wave tomography and studied its relations with the Ms 8.0 earthquake in Wenchuan, southwestern China. Our results suggest that the Longmen Shan fault belt is a rheologic boundary between the eastern Tibetan plateau and the Sichuan basin, and the deep crust of the entire Longmen Shan is significantly thickened by ductile deformation. The upper structure of the eastern Tibetan plateau is cored by the high-velocity Pengguan mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…These features reflect that the Sichuan basin is filled with thick sediments at shallow depth, and velocity gradually increases with depth, while beneath the eastern Tibetan plateau, an active orogen with a shallow depth of bedrock, S-wave velocities are relatively high since seismic velocities of sediments are much slower than those of crystalline rocks; then in the mid-lower crust, a low-velocity layer exhibits. Similar results can be found in the tomographic images by Li et al (2009) andXu et al (2010) that they also gave the general features of the velocity distribution in the eastern Tibetan plateau and the Sichuan basin, but without in the northeastern Tibetan plateau. As shown in our 3-D S-wave velocity maps, we can see a distinct revelation to the velocity distribution of the southern Ordos craton and the northeastward extension of the low-velocity layer from the Songpan-Ganzi terrane to the south of the Ordos craton.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These features reflect that the Sichuan basin is filled with thick sediments at shallow depth, and velocity gradually increases with depth, while beneath the eastern Tibetan plateau, an active orogen with a shallow depth of bedrock, S-wave velocities are relatively high since seismic velocities of sediments are much slower than those of crystalline rocks; then in the mid-lower crust, a low-velocity layer exhibits. Similar results can be found in the tomographic images by Li et al (2009) andXu et al (2010) that they also gave the general features of the velocity distribution in the eastern Tibetan plateau and the Sichuan basin, but without in the northeastern Tibetan plateau. As shown in our 3-D S-wave velocity maps, we can see a distinct revelation to the velocity distribution of the southern Ordos craton and the northeastward extension of the low-velocity layer from the Songpan-Ganzi terrane to the south of the Ordos craton.…”
Section: Discussionsupporting
confidence: 88%
“…A very low-velocity anomaly is observed in the shallow crust of the Sichuan basin on the profile BB' due to its very thick sedimentary covers. This low-velocity anomaly is also reported by previous researches derived from different observations (e.g., Xu et al, 2010;Zhang et al, 2010;Li et al, 2009). On this profile, we can also see an S-wave low-velocity layer at the depth ~20 to 40 km that only appears beneath the Songpan-Ganzi terrane and terminates at the west edge of the stable Sichuan basin.…”
Section: -D S-wave Velocity Structuresupporting
confidence: 75%
“…Some scholars argue that the occurrence of earthquakes within the fault zone is related to the crustal structure and accumulation of stress. Strong high-speed, high-resistance bodies within the upper crust can accumulate a rather large amount of stress, and earthquakes readily occur in high-resistance bodies above low-resistance bodies within the crust or the electrical mutation belt (Pei et al 2010;Wang et al 2011;Xu et al 2010). As indicated by the earthquakes in Danjiang, Gucheng, and Dangyang, earthquakes easily occur during the period in which the earth resistivity tends to first decrease and then increase (Feng et al 2013;Zhang et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Zhu and Yuan [47] simulated the dynamic spontaneous rupture process of the 2008 Mw 7.9 Wenchuan earthquake using a two-dimensional finite element method and concluded that the crustal material strength difference between the hanging wall and the footwall of the LMSF is a key factor leading to the unilateral propagation. Additionally, based on seismic tomography, Xu et al [45] found a sharply-contrasting zone compared to the surroundings, with low Vp and Vs and high Poisson's ratio anomalies in the upper crust of the central LMSF region, which was interpreted to be associated with fluid-bearing ductile flow (weak and ductile crust) and act as a barrier for the 2008 Mw 7.9 Wenchuan co-seismic rupture. Our inversion results show that before the 2008 Mw 7.9 Wenchuan earthquake, the "seismic gap" segment in the central LMSF was fully coupled at a relatively shallow depth (<5 km) (Figure 3a), and only partially-coupled or creeping at the middle depth (5-20 km).…”
Section: Unilateral Rupture Propagation Of the 2008 Mw 79 Wenchuan Ementioning
confidence: 99%
“…The kinematic rupture process of the 2008 Mw 7.9 Wenchuan earthquake shows a unilateral propagation to the northeast (e.g., [2,9,10,44]), which was reported to be caused by the effect of the crustal material strength (e.g., [45][46][47]). Zhu and Yuan [47] simulated the dynamic spontaneous rupture process of the 2008 Mw 7.9 Wenchuan earthquake using a two-dimensional finite element method and concluded that the crustal material strength difference between the hanging wall and the footwall of the LMSF is a key factor leading to the unilateral propagation.…”
Section: Unilateral Rupture Propagation Of the 2008 Mw 79 Wenchuan Ementioning
confidence: 99%